THE IMPACT OF MICROBIOTA STATUS ON COGNITIVE FUNCTIONS OF THE BRAIN - Voronina Natalya Vladimirovna (Journal Park Publishing, 2025)
The human microbiota has emerged as a critical regulator of brain function through complex bidirectional communication pathways collectively known as the gut–brain axis. Increasing evidence suggests that the composition and functional state of the intestinal microbiota significantly influence cognitive processes, including learning, memory, attention, and executive function. Alterations in microbial diversity and balance, commonly referred to as dysbiosis, have been associated with neuroinflammation, impaired neurotransmitter synthesis, disruption of the blood–brain barrier, and altered immune signaling, all of which may negatively affect cognitive performance. This article aims to analyze the impact of microbiota status on cognitive functions of the brain by examining current experimental and clinical evidence. Particular attention is given to microbial modulation of neurotransmitter production, short-chain fatty acid signaling, immune-mediated pathways, and hypothalamic–pituitary–adrenal axis regulation. The role of dysbiosis in neurodegenerative and neuropsychiatric disorders associated with cognitive decline is also discussed. Understanding the mechanisms linking microbiota alterations to cognitive function may open new perspectives for preventive strategies and microbiota-targeted therapeutic interventions aimed at preserving brain health and cognitive performance.
Keywords: Gut–brain axis, microbiota, cognitive function, dysbiosis, neuroinflammation, neurotransmitters, short-chain fatty acids.